Surveillance Bronchoscopy: Is It Still Relevant? - Benzimra, Mark (Seminars in Respiratory and Critical Care Medicine, 2018)
The performance of bronchoscopy with bronchoalveolar lavage and transbronchial biopsy is an essential tool and skill required by any clinician caring for patients postlung transplantation. Making a confident diagnosis is crucial in initiating different treatment strategies which may be in turn hazardous to the patient in light of an inaccurate diagnosis. Having more information available for evaluation optimizes the chances of tailoring appropriate therapeutic options in this complex patient population. Performing a bronchoscopy with bronchoalveolar lavage and transbronchial biopsy indeed provides a wealth of information via microbiological, cytological, and histological samples that assist us to differentiate infection from rejection, or to confirm the presence of both. This review aims to discuss the utility of bronchoscopy postlung transplantation in the diagnosis of rejection, infection, and airway complications, as well as looking into the ongoing controversy regarding monitoring practices worldwide and safety concerns.
Keywords: bronchoscopy; lung transplantation; transbronchial biopsy; rejection; monitoring